TRESK channel contribution to nociceptive sensory neurons excitability: modulation by nerve injury - Serra Jordi; Saiani Barbara; Cokic Barbara; Callejo Gerard; Tulleuda Astrid; Gasull Xavier (SAGE Publishing, 2011)
Abstract Background Neuronal hyperexcitability is a crucial phenomenon underlying spontaneous and evoked pain. In invertebrate nociceptors, the S-type leak K+ channel (analogous to TREK-1 in mammals) plays a critical role of in determining neuronal excitability following nerve injury. Few data are available on the role of leak K2P channels after peripheral axotomy in mammals. Results Here we describe that rat sciatic nerve axotomy induces hyperexcitability of L4-L5 DRG sensory neurons and decreases TRESK (K2P18.1) expression, a channel with a major contribution to total leak current in DRGs. While the expression of other channels from the same family did not significantly change, injury markers ATF3 and Cacna2d1 were highly upregulated. Similarly, acute sensory neuron dissociation (in vitro axotomy) produced marked hyperexcitability and similar total background currents compared with neurons injured in vivo. In addition, the sanshool derivative IBA, which blocked TRESK currents in transfected HEK293 cells and DRGs, increased intracellular calcium in 49% of DRG neurons in culture. Most IBA-responding neurons (71%) also responded to the TRPV1 agonist capsaicin, indicating that they were nociceptors. Additional evidence of a biological role of TRESK channels was provided by behavioral evidence of pain (flinching and licking), in vivo electrophysiological evidence of C-nociceptor activation following IBA injection in the rat hindpaw, and increased sensitivity to painful pressure after TRESK knockdown in vivo. Conclusions In summary, our results clearly support an important role of TRESK channels in determining neuronal excitability in specific DRG neurons subpopulations, and show that axonal injury down-regulates TRESK channels, therefore contributing to neuronal hyperexcitability.